Assessment of dirt impacts on photovoltaic modules in electricity generation - Franchi, Diogo; Cirolini Cervo, Enzo; Miotto, Maicon; Gonzatti, Frank; Alberto Farret, Felix (Latin American Journal of Energy Research, 2025)
This article analyzes the impact on the performance of photovoltaic (PV) modules due to the accumulation of dirt on their surface under different cleaning maintenance routines. PV modules were analyzed with varying maintenance periods, ranging from more than 4 years without cleaning to quarterly and semiannual routines. The results showed a 3.29% difference in energy generation between the modules subjected to the highest and lowest cleaning frequencies. Furthermore, it was observed that natural cleaning methods, such as precipitation, were effective only in removing light particles, such as dust, but not in removing more adherent dirt on the module surface. In subsequent experiments, it was found that modules without maintenance for up to 21 days showed insignificant generation losses, while significant losses began to occur after 45 days, and stabilizing after about 5 months.
Keywords: Photovoltaic system; dirt; maintenance; cleaning